Efficacy of transcranial direct current stimulation for improving postoperative quality of recovery in elderly patients undergoing lower limb major arthroplasty: a randomized controlled substudy - Tao, Mingshu; Yang, Jie; Liu, Rongguang; Zhang, Song; Han, Yuan; Li, Chunyan; Wei, Qi; Chen, Dexian; Fang, Jiaxing; Zhang, Hongxing; Wang, Yuwei; Liu, He; et al. (Frontiers in Neurology, 2024)
Background: Previous studies have demonstrated improvements in motor, behavioral, and emotional areas following transcranial direct current stimulation (tDCS), but no published studies have reported the efficacy of tDCS on postoperative recovery quality in patients undergoing lower limb major arthroplasty. We hypothesized that tDCS might improve postoperative recovery quality in elderly patients undergoing lower limb major arthroplasty.Methods: Ninety-six patients (≥65 yr) undergoing total hip arthroplasty (THA) or total knee arthroplasty (TKA) were randomized to receive 2 mA tDCS for 20 min active-tDCS or sham-tDCS. The primary outcome was the 15-item quality of recovery (QoR-15) score on postoperative day one (Т2). Secondary outcomes included the QoR-15 scores at the 2nd hour (T1), the 1st month (Т3), and the 3rd month (Т4) postoperatively, numeric rating scale scores, and fatigue severity scale scores.Results: Ninety-six elderly patients (mean age, 71 yr; 68.7% woman) were analyzed.Higher QoR-15 scores were found in the active-tDCS group at T2 (123.0 [114.3, 127.0] vs. 109.0 [99.3, 115.3]; median difference, 13.0; 95% CI, 8.0 to 17.0; P < 0.001). QoR-15 scores in the active-tDCS group were higher at T1 (P < 0.001), T3 (P = 0.001), and T4 (P = 0.001). The pain scores in the active-tDCS group were lower (P < 0.001 at motion; P < 0.001 at rest). The fatigue degree scores were lower in the active-tDCS group at T1 and T2 (P < 0.001 for each).undergoing lower limb major arthroplasty.